Employing Public Relations Practitioners Social Media: Jordanian Commercial Sector as A Model - Mazahera, Manal (Jordan Journal of Social Sciences, 2020)
This study aims to find out the extent of employing public relations practitioners of the social media in the commercial sectors in Jordan, and the factors affecting their use of social media tools in the lights of the five elements of the unified theory of Acceptance and use of Technology (UTAUT).The study belongs to the field of descriptive studies, which is considered one of the most appropriate research field to describe phenomena or problems by using survey methodology to identify the extent of social media usage by public relations practitioners in the commercial sector in Jordan. The researcher use a purposive sample consisting of (100) public relations practitioners. The results show that (48%) of public relations practitioners used social media in their works, The Facebook network is the most widely used among practitioners, also the study found a relationship between the expected performance and behavioral intention. The study indicates a relationship between each of the expected performance, the expected effort and the society impact. similarly, there is a relationship between the expected effort, the impact of the community and the facilities available and finally, the existence of a correlation between the society impact and the facilities available